3ΛH and 3Λ[bar]H[bar] production in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Oyama, Ken; et al. (Physics letters, 2016)
The production of the hypertriton nuclei HΛ3 and H‾Λ¯3 has been measured for the first time in Pb-Pb collisions at sNN=2.76 TeV with the ALICE experiment at LHC. The pT-integrated HΛ3 yield in one unity of rapidity, dN/dy×B.R.(HΛ3→He3,π−)=(3.86±0.77(stat.)±0.68(syst.))×10−5 in the 0-10% most central collisions, is consistent with the predictions from a statistical thermal model using the same temperature as for the light hadrons. The coalescence parameter B3 shows a dependence on the transverse momentum, similar to the B2 of deuterons and the B3 of 3He nuclei. The ratio of yields S3=HΛ3/(He3×Λ/p) was measured to be S3=0.60±0.13(stat.)±0.21(syst.) in 0-10% centrality events; this value is compared to different theoretical models. The measured S3 is compatible with thermal model predictions. The measured HΛ3 lifetime, τ=181−39+54(stat.)±33(syst.)ps is in agreement within 1σ with the world average value.